Promotions, demotions, halo effects and earnings dynamics of American executives - Christian Belzil; Michael Bognanno (Institute for the Study of Labor (IZA), 2005)
This paper explores the dynamics of wage growth in corporate hierarchies. Using panel data techniques, we estimate the causal effect of current and past transitions in reporting level and past earnings growth on components of current earnings and earnings growth using a large panel of US executives. After conditioning on unobserved heterogeneity, current compensation growth is positively correlated with past promotion outcomes but negatively correlated with past compensation growth. In a flexible model of wage growth, there is an important asymmetry between the effect of a promotion and a demotion. The effect of promotion is smaller in magnitude than the effect of a demotion. The causal effect of a promotion is positive on both growth in base pay and total cash compensation but is negative on bonus growth. The effect of a demotion is negative on growth in all pay components.
Keywords: C33; J41; M5; M51; 330; earnings growth; promotions; halo effects; hierarchies; internal labor markets; Vergütungssystem; Leistungsorientierte Vergütung; Lohnstruktur; Hierarchie; Erwerbsverlauf; USA